Scooby-Doo! World of Mystery 39 Slovakia - Orava Castle - Creative Plus Publishing Ltd (De Agostini Uk Ltd, 2005)
The gang visit a creepy castle in Slovakia and are spooked by themselves - or so it seems!
Keywords: Juvenile literature-Fiction